Early antiretroviral therapy and daily pre‐exposure prophylaxis for HIV prevention among female sex workers in Cotonou, Benin: a prospective observational demonstration study. Issue 11 (22nd November 2018) - Mboup, Aminata; Béhanzin, Luc; Guédou, Fernand A; Geraldo, Nassirou; Goma‐Matsétsé, Ella; Giguère, Katia; Aza‐Gnandji, Marlène; Kessou, Léon; Diallo, Mamadou; Kêkê, René K; Bachabi, Moussa; Dramane, Kania; et al.
Abstract: Introduction: In sub‐Saharan Africa, HIV prevalence remains high, especially among key populations. In such situations, combination prevention including clinical, behavioural, structural and biological components, as well as adequate treatment are important. We conducted a demonstration project at the Dispensaire IST, a clinic dedicated to female sex workers (FSWs) in Cotonou, on early antiretroviral therapy (E‐ART, or immediate "test‐and‐treat") and pre‐exposure prophylaxis (PrEP). We present key indicators such as uptake, retention and adherence. Methods: In this prospective observational study, we recruited FSWs from October 4th 2014 to December 31st 2015 and followed them until December 31st 2016. FSWs were provided with daily tenofovir disoproxil fumarate/emtricitabine (Truvada ® ) for PrEP or received a first‐line antiretroviral regimen as per Benin guidelines. We used generalized estimating equations to assess trends in adherence and sexual behaviour. Results: Among FSWs in the catchment area, HIV testing coverage within the study framework was 95.5% (422/442). At baseline, HIV prevalence was 26.3% (111/422). Among eligible FSWs, 95.5% (105/110) were recruited for E‐ART and 88.3% (256/290) for PrEP. Overall retention at the end of the study was 59.0% (62/105) for E‐ART and 47.3% (121/256) for PrEP. Mean (±SD) duration of follow‐up was 13.4 (±7.9) months for E‐ART and 11.8 (±7.9) months for PrEP. Self‐reported adherence was over 90% among most E‐ART participants. For PrEP, adherence was lower and the proportion with 100% adherence decreased over time from 78.4% to 56.7% ( p ‐trend < 0.0001). During the 250.1 person‐years of follow‐up among PrEP initiators, two seroconversions occurred (incidence 0.8/100 person‐years (95% confidence interval: 0.3 to 1.9/100 person‐years)). The two seroconverters had stopped using PrEP for at least six months before being found HIV‐infected. In both groups, there was no evidence of reduced condom use. Conclusions: This study provides data on key indicators for the integration of E‐ART and PrEP into the HIV prevention combination package already offered to FSWs in Benin. PrEP may be more useful as an individual intervention for adherent FSWs rather than a specific public health intervention. E‐ART was a more successful intervention in terms of retention and adherence and is now offered to all key populations in Benin. Study registration: ClinicalTrials.gov NCT02237